Volumetric modulated arc therapy based total body irradiation: Workflow and clinical experience with an indexed rotational immobilization system. (October 2017) - Ouyang, Luo; Folkerts, Michael; Zhang, You; Hrycushko, Brian; Lamphier, Richard; Lee, Pam; Chambers, Eric; Ramirez, Ezequiel; Reynolds, Robert; Yan, Yulong; Jiang, Steve B.; Timmerman, Robert; et al.
Abstract: An indexed rotational immobilization system was developed for supine total body irradiation (TBI). Treatment plans had multi-isocentric volumetric modulated arc therapy (VMAT) beams to the upper body and parallel-opposed fields to the lower body, with a 12 Gy prescription dose to >90% of the body and mean lung dose ∼8 Gy. In the end-to-end test, point dose measurements had <10% error. Compared to conventional TBI, the VMAT-based TBI technique increased the mean dose to the body by ∼1.0–1.5 Gy and decreased the mean dose to the lung by ∼1.0–1.5 Gy. Overall treatment time was ∼1.5 h, similar to conventional TBI.